Psycometric Test of Indonesian version of The Self-rated Fall Risk Questionnaire in Elderly Community - Salsabila, Dika Tiara; Komalasari, Dwi Rosella (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Falls are common problem and often occur in the elderly due to decreased body abilities, so a valid and consistent Instrumen is needed to see how high the risk of falls is in the elderly with the Self-rated Fall Risk Questionnaire (SRFQ). So, the practical application of this questionnaire is to pay attention to the dangers of environmental conditions regarding falls in the elderly and support the family to avoid the risk of falls in the elderly which can occur due to decreased balance disorders and the need for physiotherapy. Determining the validity and reliability of the Self-rated Fall Risk Questionnaire’s Indonesian version was the goal of this study. This study was in the methodological study that conducted in September 2023 at Elderly Community Gonilan village, Sukoharjo. There were 58 subjects. Participation this study that choosen by purposive sampling. The SRFQ was given 2 times with an interval of 2 weeks. Between the two measurement sessions, the Indonesian version of the SRFQ test-retest reliability results were very good (ICC 0,989, p-value < 0,001, and 95% CI: 0,982-0,994). Good Internal Consistency was a Cronbach’s Alpha value was 0,829. Based on the content validity results shown, the corrected correlation item value was below 0,3. There were 3 items. Concluded was that the Indonesian version of the SRFQ is declared reliable, but the content validity of the 3 items needed to be retested.